A mixed-methods investigation for effects of built environments on older people’s social interaction in care homes - Wang, Chendi; Pan, Yujian; Li, Xingjian; Qiang, Shaohua (Frontiers in Public Health, 2025)
This study examines relationships between the built environment (BE) and social interaction (SI) among older adults in care homes. A mixed-methods design combined questionnaires (n = 119), environmental measurements, and behavioral observations across three care homes. An integrated BE-SI model, developed using multivariate statistical analyses, identified key environmental determinants of SI. Results indicate that recreational spaces, lighting, functional facilities, and accessibility significantly influenced interpersonal interactions, activity engagement, resident-caregiver relations, and conflict. Objective environmental measures corroborated survey and observational findings: care homes with larger recreational areas and improved functional accessibility showed higher frequencies of resident social engagement. These findings highlight the critical role of environmental design in promoting social participation among older residents. The study offers evidence-based recommendations for designers, facility managers, and policymakers to create age-friendly care-home environments that foster social interaction and enhance residents’ wellbeing. The BE-SI model provides a practical framework for future research, facility evaluation, and policy implementation.